Effect of staggered housing layout on internal airflow of houses in Malaysia - Abdul Majid, Noor Hanita; Hokoi, Shuichi; Sapian, Abdul Razak (2007)
The paper presents the airflow studies due to staggered layout at proposed new terrace housing concept in Malaysia. The importance of internal airflow to thermal comfort and indoor air quality of the terrace houses is indisputable (Hui,1998). The internal airflow contributes to cool the human body through evaporation process and indoor air quality through air exchange in the internal spaces. this research suggests that the staggered layout as implemented in the traditional villages is important to facilitate airflow and consequently improve the thermal conditioned of the internal spaces (Lim, 1987). The field data of the parameters related to thermal comfort at the Malay traditional houses and existing terrace houses are used as a basis for comparison on the performance of the airflow at the new proposed layout. Verification of the new proposed concept is done through airflow simulation using CFD method (Abdul Razak and Nurul Asyikin, 2004). Airflow is chosen as an indicator due to its imperative contribution to thermal comfort in the hot humid climate. the research found some improvement to the airflow performance that is foreseen to be a positive contributor to the thermal comfort and indoor air quality performance at the new proposed terrace housing concept.